(untitled) (Al-Academy, 2016)
Recent studies have tended to look at Mottagorat texts for seeking more of the information provided by the book for the reader, has been known by several terms Mottagorat texts, including thresholds, including the margins of the text and the parallel texts, and came this difference, according to researchers who ate the subject of research and investigation. Thus, the researchers assert that all these texts must be subjected to provide information even if propaganda of the text. Hence arose the importance of these texts in Informatics scientific material being wrapped body of the text as well as being propaganda material to evoke the recipient to read, and then to the importance of this topic, the search came on five chapters, the first chapter dealt with the researcher and the research problem, which was: What are the signs suggestive texts involved in parallel to the original text, a screenplay? The goal of the present study is to detect signs suggestive texts carried by parallel scenario surrounding the film. Chapter II also included a theoretical framework has been divided on the two themes: First, the parallel nature of the text. And second, sections and types of parallel texts. The third quarter was the search procedures, as was the research methodology is descriptive analytical method, and was the research sample is a scenario that did not (the trial). The fourth chapter is an analysis of the research sample also came fifth chapter of the findings and conclusions, the most important were:fundamental value to create meaning in the title is the font size, color, and location of the space of the interface cover, as it was the title of the research sample demonstrates the substance of the conflict through its sheer size, which, if anything, it shows the magnitude of the disaster suffered by the hero, as well as the font color was red which demonstrates the crime, murder, and others, such as the rise of so authoritarian regime will inevitably be at the expense of the fates of people and blood